Aldegondabreen glacier change since 1910 from structure-from-motion photogrammetry of archived terrestrial and aerial photographs: utility of a historic archive to obtain century-scale Svalbard glacier mass losses - Erik Schytt Holmlund (Journal of Glaciology, 2021)
Photogrammetric reconstructions of the Aldegondabreen glacier on Svalbard from 17 archival terrestrial oblique photographs taken in 1910 and 1911 reveal a past volume of 1373.7 ± 78.2 · 106 m3; almost five times greater than its volume in 2016. Comparisons to elevation data obtained from aerial and satellite imagery indicate a relatively unchanging volume loss rate of − 10.1 ± 1.6 · 106 m3 a−1 over the entire study period, while the rate of elevation change is increasing. At this rate of volume loss, the glacier may be almost non-existent within 30 years. If the changes of Aldegondabreen are regionally representative, it suggests that there was considerable ice loss over the entire 1900s for the low elevation glaciers of western Svalbard. The 1910/11 reconstruction was made from a few of the tens of thousands of archival terrestrial photographs from the early 1900s that cover most of Svalbard. Further analysis of this material would give insight into the recent history and future prospects of the archipelago's glaciers. Photogrammetric reconstructions of this kind of material require extensive manual processing to produce good results; for more extensive use of these archival imagery, a better processing workflow would be required.